Teo-Ekologi Hindu Dalam Teks Lontar Sri Purana Tatwa - Acyutananda Wayan Gaduh; Hari Harsananda (Kamaya: Jurnal Ilmu Agama, 2021)
The agricultural sector in Bali is increasingly unpopular for the younger generation. This condition is inversely proportional to the increasing need for food and the tourist destination of Bali in the form of beautiful rice fields. Hindu agricultural traditions make the profession of farmers not only as a source of income but also as a medium for preserving the natural environment through the Hindu theo-ecology concepts. This study tries to explore Hindu theo-ecological in the Lontar Sri Purana Tattwa. The method used is a literature study technique by utilizing hermeneutic theory and interpretive theory which emphasizes the interpretation dimension of values ​​in the Lontar Sri Purana Tattwa. Lontar Sri Purana Tattwa explained the teachings of Hindu theo-ecology through the concept of divinity, ritual, ethics, and mythology. God is manifested as Saguna Brahman, namely gods and goddesses who control various aspects of nature. The main deity worshiped is Dewi Sri as the ruler of rice and welfare. Ritual practices are carried out massively and ethics in farming are upheld. The Hindu theo-ecology in the Sri Purana Tattwa makes professions (farmers) a medium to get closer to God, and at the same time preserve nature. Through an understanding of Hindu theo-ecology, it is hoped that it can increase the interest of the Hindu community in the agricultural sector and foster a love for the environment.